Tokyo fears rhapsody. 1 - Sugito, Akira (VIZ Media, 2025)
Hachiro is the mightiest monster around, created to strike terror into humanity! But a chance encounter with ice cream makes him an instant fan of human culture, earning him the ire of his fellow Fears. Between rebelling against his overbearing creator and slaughtering ghoulish foes, Hachiro's got a lot more than just ice cream on his plate! Hachiro keeps his true identity as a Fear a secret while working odd jobs-until he sees the Unbelievables, a newly established mecha-suited unit of the Metro PD. Now he wants to be just as cool as they are! But are there limits to what a monster can do?